VILLAGE GOVERNMENT LEGAL POLICIES IN INFORMATION TECHNOLOGY-BASED PUBLIC SERVICES - Gufran; Aman Ma'arij; Hajairin (Sekolah Tinggi Ilmu Hukum Awang Long, 2023)
The legal policy of the village government in information technology-based public services, in general, is currently not running optimally. Even though technological developments must be utilized by all elements of society including the village government, several programs can be carried out include such as E-Village, village fund information, village websites, and being able to develop applications that can be used to provide public services to village communities and so on. The research aims to find out whether information technology-based integrated criminal justice system policies can become an instrument for eradicating corruption. The research method used is normative legal research with statutory approaches, theoretical approaches, and comparative and conceptual approaches. The findings in this study are that first, the village government law as stipulated in Law Number 6 of 2014 concerning Villages, cannot be fully explained by village officials, including utilizing technological advances in maximizing public services for the community, so that the community gets information and services that are easy. Second, developing an internet-based rural information network by building village websites with the desa.id domain, encouraging technology-independent villages, improving public services with the village partner application, and managing resources based on village profiles with resource surveys and geospatial data with the village granary application. see mitra.or.id) and build villages with interconnected systems and regulations that support villages to take development initiatives.